CLIL on the spot: migrant education in Greece - Mattheoudakis, Marina; Fotiadou, Georgia; Papadopoulou, Despina (Frontiers in Education, 2025)
IntroductionThis study aims to explore the instructional strategies employed by Greek teachers in primary and secondary school classes attended by large numbers of refugee and migrant students. As there is not a clear methodological ‘blueprint’ for CLIL that teachers are required to follow, our study will investigate which of the principles framed for the CLIL approach are in fact applied by educators.MethodsTo this aim, we adopted a survey-based research methodology (web-based questionnaire) and a phenomenological approach (semi-structured interviews).ResultsResults include data from 125 respondents of the questionnaire, working in 21 different regional units of Greece, and the lived experiences of five educators. Most of the participants had no prior training in bilingual or intercultural education but were highly qualified (holders of at least an MA). Thus, although educational background was not identified as a predictive factor to the teaching strategies, training in topics such as bilingual education and interculturality was. Scaffolding techniques were significantly affected by teachers’ age, training and educational setting (primary vs. secondary). Moreover, the variety of activities offered differed between the two levels of school settings as educators chose strategies they deemed appropriate for the cognitive and proficiency level of their students.DiscussionOverall, our findings suggest that, although educators of Greek state schools lack specific training in managing plurilingual and pluricultural classes, they experiment with a variety of CLIL practices and that those who have had some relevant trainings are more prompt to support their students with multiple scaffolding techniques than those who have had no such prior experience.